(untitled) (Bangladesh Journal of Botany, 2023)
Ceratoides arborescens (Losinsk.) Tsien et C. G. Ma, a species endemic to China, is widely used in ecological restoration and as fine forage due to its high drought resistance and nutrient content, respectively. Its bracts are often removed from diaspores during planting because their dense hair covering is not conducive to sowing. However, it is not clear whether the removal of bracts is beneficial to C. arborescens seed germination. A seed germination experiment was conducted to measure how bracts influence seed germination. Three diaspore treatments were used: seed bracts removed (BR), bracts removed and recombined with seeds (BRB); and seed bracts not removed (B). To further explore whether bract nutrient content affects seed germination, seeds without bracts (BR) were tested with additions of three different nutrient (Mn, Ca, and Fe) in a culture solution. It was found that BR accelerated average germination time but had no detectable effect on seed germination rate. Further, the BR significantly decreased seed germination potential and germination index. Additionally, seed germination potential and the germination index were improved by BRB, while the seedling vigor index was also enhanced. Moreover, it was found that the elements Ca, Mn, and Fe were higher in bracts than those in seeds. However, nutrient addition manipulation showed that the addition of Mn promoted seed germination. The findings of this experiment suggest that C. arborescens bracts are beneficial during planting, because they contain essential elements for germination. Removing bracts from the diaspore has no potential impact on the reduction of costs and improvement of the seed germination characters of C. arborescens. Bangladesh J. Bot. 51(4): 897-905, 2022 (December) Special